IMPLEMENTATION OF EDUCATIONAL FINANCING MODELS IN HIGH-QUALITY EDUCATIONAL INSTITUTIONS - Rifa'i, Moh; Wardaniah; Yuni Rohimatus Syamsiyah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
The implementation of financing models in educational institutions generally relates to the management of financial resources to ensure operational sustainability and the improvement of educational service quality. An effective and efficient financing model is one that contributes to service quality enhancement, enables the achievement of targeted outcomes, supports human resource empowerment, fosters community participation, and strengthens the stability and long-term sustainability of educational institutions. This study employs a qualitative research approach, specifically descriptive qualitative design. Informants include the leadership and caretakers of Pondok Pesantren Al-Mashduqiah, as well as human resources within the finance and facilities directorates, selected through purposive sampling and supplemented with snowball sampling. Data analysis consists of data collection, reduction, display, and conclusion drawing.Findings reveal that Pondok Pesantren Al-Mashduqiah s a hybrid financing scheme combining the Public-Private Partnership (PPP) model and the Need-Based Financing Model. Implementation is carried out through systematic need assessments of institutional units, PPP planning based on these assessments, integrated budgeting that combines BOS funding, regional/national government budgets (APBD/APBN), government grants, donor support through UPIZ Al-Mashduqiah, private sector contributions (DUDI), foundation funds, and independent economic initiatives, followed by continuous monitoring and evaluation aligned with financing targets.